Penerapan Biogas Guna Mengurangi Pencemaran Lingkungan di Kelompok Tani Ternak: Application of Biogas to Reduce Environmental Pollution in Livestock Farmers - Sujono, Sujono; Kusuma, Hendra (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
This biogas technology program aims to reduce environmental pollution due to the smell of livestock manure and, at the same time, reduce the household economic costs of the farmer group community to buy LPG. The service method is by providing education to farmer groups about the cultivation of beef and dairy cattle, manure as a source of energy and fertilizer, and demonstration plots for biogas production. As the result of the dedication to making Biogas with a capacity of 12 m3, the digester starts to produce gas on the 14th day after being filled with cow dung. The economic value of cooking using Biogas is that it saves rupiah by not buying LPG gas, so on average, it holds 4-5 3 kg LPG cylinders per week or 16-20 LPG cylinders per month. The economic value saved is IDR 320,000 – 400,000 per family per month that uses this biogas fuel. Farmer groups use biogas waste as fertilizer for vegetables and corn. Three main benefits are felt, Biogas as a substitute for LPG, which the community has used. The by-product of Biogas has been used as organic fertilizer. From a social perspective, this program has also educated the public that livestock manure, which the community has considered waste, can provide economic and environmental benefits. The by-product of biogas technology which is processed into solid organic fertilizer, can increase soil nutrients, save costs on purchasing fertilizer, and increase people’s income.